High SVR rate following retreatment of non-sustained virological responders to sofosbuvir based anti-HCV therapies regardless of RAS testing: A real-life multicenter study. (2nd September 2019) - Darweesh, Samar K.; Elsaeed, Kadry; Omar, Heba; El Raziky, Maissa; Elakel, Wafaa; Elserafy, Magdy; Ismail, Sohier Ahmed; Gomaa, Ahmed A.; Mehrez, Mai; El Kassas, Mahamed; Abdullah, Mohamed; Shaker, Mohammed Kamal; et al.
ABSTRACT: Aim : Evaluation of the efficacy and safety of sofosbuvir/daclatasvir/ribavirin (SOF/DCV/RBV) in treating non-sustained virological responders (non-SVR12) to prior sofosbuvir-based therapy, in absence of RAS testing in mass treatment, and determination of the optimal timing to start re-treatment. Methods : Real-life prospective observational study included prior non-responders to 24-weeks SOF-RBV (n = 679, 67%) or 12-weeks SOF- RBV- PEG (n = 335, 33%). Patients were re-treated with daily SOF/DCV/RBV for 12 (n = 270) or 24 weeks (n = 744). The primary efficacy endpoint was SVR12. The primary safety endpoints were reported adverse events (AEs) from baseline to SVR12 time point. Results : We included 1, 014 patients [age 52 ± 9 years, 58.48% men]. Cirrhosis was documented in 46.98% and 27.5% of SOF-RBV and SOF-RBV-PEG non-responders respectively. Overall, SVR12 was 90.6% [92.2% for 12 weeks therapy and 90.05% for 24 weeks therapy]. Mild AEs occurred in 5.13% (n=52) and 3.1% (n=32) discontinued treatment including eight on-treatment mortalities. Higher baseline FIB-4 and shorter interval before starting retreatment (<6 months) were independent predictors of non-SVR12 on multivariate regression analysis. Conclusion: SOF/DCV/RBV is an effective and safe treatment option for non-responders to prior sofosbuvir-based therapy. Six months interval before retreatment is optimal for achieving favorable SVR.